Performance, Carcass Yield and Stress Level of Broilers Receiving a Ginger-Based Product in Diets with or Without Iodine - Cardinal , Katia Maria; Moraes, Priscila de Oliveira; Pires, Paula Gabriela da Silva; Vilella, Lucas de Marques; Prato, Brenda Santaiana; Ribeiro, Andrea Machado Leal (International Journal of Poultry Science, 2020)
Background and Objective: Ginger has potential to be used in chicken nutrition because it exhibits several positive characteristics, such as being an antioxidant agent and possesses medicinal properties against digestive disorders. This study was conducted to evaluate the effect of a ginger-based product in diets with or without iodine addition on performance, carcass yield and stress level of broilers. Materials and Methods: Performance, carcass yield and stress level of broilers fed diets with ginger supplementation with or without iodine were evaluated. A total of 300 broilers were raised from 1-42 days. Groups of 10 broilers were distributed in 30 pens with feed and water ad libitum. The experiment consisted of three treatments: control diet, control diet with ginger and iodine and control diet with ginger and without iodine. Diets were formulated in starter, grower and finisher phases. Body weight, feed intake and feed conversion ratio were evaluated. Twenty birds per treatment were slaughtered to evaluate cuts and carcass yield, blood was collected of eight birds per treatment to analyze leukocytes, lymphocytes, heterophile and calculate heterophile to lymphocyte (H/L) ratio and behavior was observed. Data were analyzed using ANOVA and means were compared by Lsmeans. Results: No effects (p>0.05) were observed on feed intake, weight gain and feed conversion ratio in any periods, as well in commercial cuts and carcass yield. Treatments did not influence leukocytes, lymphocytes, heterophile and H/L (p>0.05) and animals showed no difference in behavior. Conclusion: The ginger supplemented in diets with or without iodine do not affect growth performance, carcass and commercial cuts yield. As well as do not affect broiler stress level.